Pengaruh Kepemimpinan dalam Memanajemen Perubahan Organisasi Studi Kasus (PT Bhinivan Konstruksi Abadi) Pematang Seleng - Wiranti Wiranti; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
In this journal the author wants to analyze how the influence of leadership in the work environment is how employees can work in accordance with the instructions that have been given to them, by ignoring them. In order to achieve satisfactory results and there are no desired obstacles, the influence of the head of the Pt Bhinivan Construction Abadi bascamp is very much needed, to always give calls that demand disciplined work, in order to maintain the safety, comfort, and security of the workers. Management of change is needed to improve the nature of the workers who sometimes do not want to listen to the advice that has been given to protect themselves and the company for the better. And in getting the data the author uses the descriptive method, which in this study the author wants to provide information about the problems, circumstances, structure of the institution, service or program, which is owned by the leader in improving performance at PT Bhinivan Konstruksi Abadi (BKA)